New Directions in Agricultural Communications Curricula - Eugene A. Kroupa; James Evans (Journal of Applied Communications, 1973)
The title of this address - "New Directions in Agricultural Communications Curricula" - might better be paraphrased as sifting and winnowing the grain from the chaff.